2021
DOI: 10.1101/2021.06.08.447553
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictors of cognitive impairment in primary age-related tauopathy: an autopsy study

Abstract: Primary age-related tauopathy (PART) is a form of Alzheimer-type neurofibrillary degeneration occurring in the absence of amyloid-beta (Aβ) plaques. While PART shares some features with Alzheimer disease (AD), such as progressive accumulation of neurofibrillary tangle pathology in the medial temporal lobe and other brain regions, it does not progress extensively to neocortical regions. Given this restricted pathoanatomical pattern and variable symptomatology, there is a need to reexamine and improve upon how P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 65 publications
(92 reference statements)
3
18
0
Order By: Relevance
“…Cerebrovascular pathology such as infarcts, microinfarcts, and hemorrhages also increase with age and may contribute to cognitive decline, particularly executive dysfunction, in ADNC and PART. 11,26 The severity of cognitive impairment often observed in individuals with PART is surprising given the low level and localized nature of the tangle pathology, even considering greater than expected hippocampal CA2 region involvement 27 or medial temporal left-right asymmetry. 28 We therefore hypothesized that other age-related copathologies such as LATE-NC or vascular pathology may play a significant role in the cognitive decline of these patients.…”
mentioning
confidence: 99%
“…Cerebrovascular pathology such as infarcts, microinfarcts, and hemorrhages also increase with age and may contribute to cognitive decline, particularly executive dysfunction, in ADNC and PART. 11,26 The severity of cognitive impairment often observed in individuals with PART is surprising given the low level and localized nature of the tangle pathology, even considering greater than expected hippocampal CA2 region involvement 27 or medial temporal left-right asymmetry. 28 We therefore hypothesized that other age-related copathologies such as LATE-NC or vascular pathology may play a significant role in the cognitive decline of these patients.…”
mentioning
confidence: 99%
“…While Braak staging is highly reproducible, with one report showing that across brains and raters the kappa score was greater than 0.90 108 , it is a semiquantitative (ordinal) variable. Further studies using a more quantitative approach to measuring tau burden that we have shown more closely align with functional clinical measures in PART may reveal additional candidates 109 . Additional follow-up studies in experimental models are necessary further to validate our findings.…”
Section: Discussionmentioning
confidence: 73%
“…2b, online resource). Comorbid cerebrovascular disease, which is common in this cohort, is likely responsible for the variation in cognitive impairment [39]. In summary, our cohort consists of older individuals, with a range of dementia severity, restricted regional tau distribution and varying severity of burden, demonstrating the diversity of both the clinical and neuropathological features of the condition.…”
Section: Resultsmentioning
confidence: 89%
“…Braak NFT staging is also modeled after a subset of AD cases with patterns of NFT formation that may differ somewhat from the pattern seen in PART. Furture studies using a more quantitative approach to measuring tau burden that we have shown more closely aligns with functional clinical measures in PART may reveal additional candidates [39].…”
mentioning
confidence: 68%